An epidemic model for SARS-CoV-2 with self-adaptive containment measures - Sabina Marchetti; Alessandro Borin; Francesco Paolo Conteduca; Giuseppe Ilardi; Giorgio Guzzetta; Piero Poletti; Patrizio Pezzotti; Antonino Bella; Paola Stefanelli; Flavia Riccardo; Stefano Merler; Andrea Brandolini; et al. (PLoS ONE, 2022)
During the COVID-19 pandemic, several countries have resorted to self-adaptive mechanisms that tailor non-pharmaceutical interventions to local epidemiological and health care indicators. These mechanisms reinforce the mutual influence between containment measures and the evolution of the epidemic. To account for such interplay, we develop an epidemiological model that embeds an algorithm mimicking the self-adaptive policy mechanism effective in Italy between November 2020 and March 2022. This extension is key to tracking the historical evolution of health outcomes and restrictions in Italy. Focusing on the epidemic wave that started in mid-2021 after the diffusion of Delta, we compare the functioning of alternative mechanisms to show how the policy framework may affect the trade-off between health outcomes and the restrictiveness of mitigation measures. Mechanisms based on the reproduction number are generally highly responsive to early signs of a surging wave but entail severe restrictions. The emerging trade-off varies considerably depending on specific conditions (e.g., vaccination coverage), with less-reactive mechanisms (e.g., those based on occupancy rates) becoming more appealing in favorable contexts.